2013
DOI: 10.1371/journal.pone.0066960
|View full text |Cite
|
Sign up to set email alerts
|

The GPVI-Fc Fusion Protein Revacept Improves Cerebral Infarct Volume and Functional Outcome in Stroke

Abstract: ObjectivesWe examined the effect of Revacept, an Fc fusion protein which is specifically linked to the extracellular domain of glycoprotein VI (GPVI), on thrombus formation after vessel wall injury and on experimental stroke in mice.BackgroundSeveral antiplatelet drugs for the treatment of myocardial infarction or ischemic stroke with potent anti-ischemic effects have been developed, but all incur a significant risk of bleeding.MethodsPlatelet adhesion and thrombus formation after endothelial injury was monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 36 publications
8
74
0
Order By: Relevance
“…In mouse models of thrombosis, pretreatment with this protein, called Revacept, was reported to prevent occlusive thrombus formation 52 and reduce infarction size after ischemic stroke. 53 These results were in agreement with those seen in GPVI-deficient mouse models, albeit less pronounced, indicating the potential efficacy of this approach. 6 Revacept is now under phase II trial (clinicaltrials.gov: NCT01645306) after phase I indicated that it is safe in healthy subjects.…”
Section: Blocking the Collagen-gpvi Interactionsupporting
confidence: 79%
“…In mouse models of thrombosis, pretreatment with this protein, called Revacept, was reported to prevent occlusive thrombus formation 52 and reduce infarction size after ischemic stroke. 53 These results were in agreement with those seen in GPVI-deficient mouse models, albeit less pronounced, indicating the potential efficacy of this approach. 6 Revacept is now under phase II trial (clinicaltrials.gov: NCT01645306) after phase I indicated that it is safe in healthy subjects.…”
Section: Blocking the Collagen-gpvi Interactionsupporting
confidence: 79%
“…Consistent with observations made in GPVI‐deficient patients, inhibition, immunodepletion, or genetic deletion of GPVI in animals only had minor consequences on primary hemostasis . In contrast to its limited impact on primary hemostasis, GPVI deficiency conferred remarkable protection against thrombosis in a variety of in vitro and in vivo experimental models, including flow chamber‐based assays using human atherosclerotic plaque material . For these reasons, and despite some controversies, GPVI has been proposed as a promising target for antithrombotic therapy with reduced bleeding risk as compared to current antiplatelet therapies based on administration of aspirin and/or P2Y12 inhibitors …”
Section: Gpvi In Primary Hemostasis and Thrombosissupporting
confidence: 56%
“…We showed previously that GPVI‐Fc inhibits platelet‐induced thrombus formation at sites of vascular injury . Administration of GPVI‐Fc improved myocardial ischemia and cerebral infarction without affecting bleeding time and inhibited progression of atherosclerosis . GPVI‐Fc also inhibited collagen‐induced aggregation in humans in a phase 1 study …”
Section: Discussionmentioning
confidence: 91%